Poverty and Civil War: Revisiting the Evidence - Djankov, Simeon; Reynal‐Querol, Marta (The Review of Economics and Statistics, 2010)
Previous research has interpreted the correlation between per capita income and civil war as evidence that poverty is a main determinant of conflict. In this paper, we find that the relationship between poverty and civil war is spurious and is accounted for by historical phenomena that jointly determine income evolution and conflict. In particular, the statistical association between poverty and civil wars disappears once we include country fixed effects. Also, using cross‐section data for 1960 to 2000, we find that once historical variables like European settler mortality rates and the population density in 1500 are included in civil war regressions, poverty does not have an effect on civil wars. These results are confirmed using longer time series from 1825 to 2000.